HUBUNGAN ANTARA PEMETAAN LINEAR DAN BILINEAR - Ruhama, Mustafa A. H. (Universitas Khairun, 2013)
Let U, V and W are vector spaces at the same field, phi : U ? V is linear mapping and is complex numbers. L (U,V) the collection of all linear mapping phi : U ? V . If V = C that is linear functional. Let phi : U ? V bilinear mapping, if W = C that phi is bilinear functional. The collection of all bilinear mapping phi : U x V ? W denoted with B(U,V,W). Based on the explanation above, problems we will discuss about relation between linear mapping, bilinear mapping and bilinear functional, some properties at bilinear mapping.